2021
DOI: 10.1007/s40820-021-00649-9
|View full text |Cite
|
Sign up to set email alerts
|

Superflexible and Lead-Free Piezoelectric Nanogenerator as a Highly Sensitive Self-Powered Sensor for Human Motion Monitoring

Abstract: For traditional piezoelectric sensors based on poled ceramics, a low curie temperature (Tc) is a fatal flaw due to the depolarization phenomenon. However, in this study, we find the low Tc would be a benefit for flexible piezoelectric sensors because small alterations of force trigger large changes in polarization. BaTi0.88Sn0.12O3 (BTS) with high piezoelectric coefficient and low Tc close to human body temperature is taken as an example for materials of this kind. Continuous piezoelectric BTS films were depos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
54
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(55 citation statements)
references
References 66 publications
1
54
0
Order By: Relevance
“…[ 172 ] By using Sr doped BaTiO 3 thin films deposited on glass fiber fabrics, we reported a superflexible PENG based self‐powered sensor that is highly sensitive to human motion monitoring. [ 173 ] Bai et al [ 91 , 93 ] have reported that the photoferroelectrics can also be used for multisource energy harvesting‐sensing.…”
Section: Emerging Energy and Environmental Applicationsmentioning
confidence: 99%
“…[ 172 ] By using Sr doped BaTiO 3 thin films deposited on glass fiber fabrics, we reported a superflexible PENG based self‐powered sensor that is highly sensitive to human motion monitoring. [ 173 ] Bai et al [ 91 , 93 ] have reported that the photoferroelectrics can also be used for multisource energy harvesting‐sensing.…”
Section: Emerging Energy and Environmental Applicationsmentioning
confidence: 99%
“…Feng et al [ 184 ] developed a motion monitoring technique for flexible integrated sensor systems that is able to independently measure bending strain and pressure coupled with a low-cost and simple manufacturing process. Yu et al [ 185 ] prepared ultra-flexible and lead-free piezoelectric nanogenerators as highly sensitive self-powered sensors for monitoring human motion, which displayed promise for applications in smart healthcare.…”
Section: Applications Of Flexible Sensorsmentioning
confidence: 99%
“…In recent years, with the rapid development of the Internet of Things (IoT) and the growing requirements of people’s life quality, various sensors used for monitoring health and environmental quality have gradually entered people’s daily lives to enhance people’s living standards [ 1 5 ]. For instance, gas sensors can be exploited to monitor the content of various gases in the environment [ 6 9 ].…”
Section: Introductionmentioning
confidence: 99%